1998
DOI: 10.4269/ajtmh.1998.59.312
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution and clinical description of leishmaniasis cases in Peru.

Abstract: Studies were conducted from 1986 through 1993 to further define the geographic distribution and relative importance of different species of Leishmania as a cause of leishmaniasis in Peru. Patients with a clinical diagnosis of cutaneous and/or mucosal or diffuse cutaneous leishmaniasis were enrolled at the Naval Medical Research Institute Detachment (NAMRID) Laboratory in Lima, the Tropical Disease Clinic at San Marcos University Daniel A. Carrión, the Central Military Hospital, and a Ministry of Health hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 21 publications
4
124
0
7
Order By: Relevance
“…3,[15][16][17] Capture of sand flies and identification. Peridomiciliary sand fly specimens were captured in September, November, and December of 2009 (before and during the rainy season) in the vicinity of 10 arbitrarily selected houses during 10 consecutive days each month (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[15][16][17] Capture of sand flies and identification. Peridomiciliary sand fly specimens were captured in September, November, and December of 2009 (before and during the rainy season) in the vicinity of 10 arbitrarily selected houses during 10 consecutive days each month (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…1 In South America, New World tegumentary leishmaniasis (NWTL) is mainly caused by species of the Viannia subgenus, including L. (V.) braziliensis, Leishmania (V.) peruviana, Leishmania (V.) guyanensis, and Leishmania (V.) panamensis. 2,3 In Peru, NWTL is endemic in 74% of the country, 3,4 and there were 6,761 reported cases in 2010. 5 The transmission cycle of Leishmania begins with the bite of an infected phlebotomine sand fly.…”
Section: Introductionmentioning
confidence: 99%
“…] panamensis infections [13]. In particular, as above-mentioned, three clinical outcomes may derive from L. [V.] braziliensis infection, probably due to the complex interactions with the host's imune system.…”
Section: Mucosal (Or Mucocutaneous) Leishmaniasismentioning
confidence: 99%
“…1,2 Among the subgenus L. (Viannia), different species are widespread in South American regions to which leishmaniasis is endemic, which include areas from the tropical jungle to Andean valleys. It has been previously demonstrated that at 12 months posttreatment, 30% of L. (V.) braziliensis-infected patients showed treatment failure with pentavalent antimony compared with 25% of L. (V.) peruviana-infected patients and 8% of L. (V.) guyanensis-infected patients, thus reiterating a species specificity to treatment response.…”
Section: Introductionmentioning
confidence: 99%